Analisis Sifat Mekanik dan Tekstur Tempe Goreng: Pengaruh Perbedaan Jenis Pembungkus (Daun Pisang vs Plastik) terhadap Karakteristik Fisikokimia - Amadea Gita Rasendriya; Siti Shabrirah; Nabila Mutiara Anzani; Putri Irma Dani; Mutia Bilqis Humaira (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
Tempe is one of the most familiar fermented soybean food products among Indonesians due to its high nutritional content and relatively simple production method. The fermentation process involves Rhizopus sp. molds, particularly Rhizopus oligosporus and Rhizopus oryzae, which break down carbohydrates, proteins, and fats into simpler, bioactive compounds. The packaging stage is a crucial factor determining physical quality, as the use of banana leaves and plastic creates different fermentation environments. This study aims to analyze the effect of packaging type on the texture characteristics of processed tempeh after frying using a food physics approach. Through experimental methods and Texture Profile Analysis (TPA) testing, this study evaluated differences in hardness and crispiness parameters as indicators of product quality. The results of this study are expected to provide theoretical and practical contributions to the food industry in optimizing the textural quality of tempeh through the selection of appropriate packaging materials.